2019
DOI: 10.1177/2042018818824215
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient self-care using diabetes technologies

Abstract: Diabetes technologies are an unstoppable phenomenon. They offer opportunities to improve patient self-care through empowerment. However, they can be a challenge for both patients and clinicians. Thus, the use of technology may empower or burden. To understand and benefit from the use of diabetes technologies, one must understand the currently unmet needs in diabetes management. These unmet needs call for perspectives beyond glycated hemoglobin and an evaluation of technology solutions. Optimal use of these tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 76 publications
(117 reference statements)
1
32
0
2
Order By: Relevance
“…Because exercise leads to fluctuations in blood glucose level, it may be difficult for children and adolescents with T1D to undertake appropriate levels of physical activity in their everyday life [27]. An effective solution can be found in the use of new technologies such as continuous glucose monitoring (CGM), either from real-time use (rtCGM) or intermittently viewed (iCGM), which offer opportunities to improve self-management, allow observation of the trends in their glycemic control, as well as prevent hypoglycemia [28]. Fear of severe hypoglycemia is still the most important barrier for children and adolescents and it can be more troublesome for them than for adults with T1D [23,29].…”
Section: Discussionmentioning
confidence: 99%
“…Because exercise leads to fluctuations in blood glucose level, it may be difficult for children and adolescents with T1D to undertake appropriate levels of physical activity in their everyday life [27]. An effective solution can be found in the use of new technologies such as continuous glucose monitoring (CGM), either from real-time use (rtCGM) or intermittently viewed (iCGM), which offer opportunities to improve self-management, allow observation of the trends in their glycemic control, as well as prevent hypoglycemia [28]. Fear of severe hypoglycemia is still the most important barrier for children and adolescents and it can be more troublesome for them than for adults with T1D [23,29].…”
Section: Discussionmentioning
confidence: 99%
“…In this digital era of connected health consumers, the interplay between theory-driven models of diabetes management and observed communication in social media is currently poorly understood [ 50 ]. Previous studies have shown that those with DSM who participate in social media forums or platforms saw a decrease in their HbA 1c (glycated hemoglobin) [ 51 ]. In the future, physicians may “prescribe” a form of social media or platform to reinforce healthy lifestyle choices outside of the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of advanced and userfriendly technologies such as the new-generation glucose sensors and insulin pumps offers promising prospects to patient self-care through empowerment [6]. These technologies allow people with T1D and caregivers to precisely and constantly measure their blood glucose (BG) concentrations and regulate insulin infusion.…”
Section: Introductionmentioning
confidence: 99%